2021
DOI: 10.12669/pjms.38.1.4545
|View full text |Cite
|
Sign up to set email alerts
|

Application of tirofiban in patients with acute myocardial infarction complicated with diabetes and undergoing emergency interventional therapy

Abstract: Objectives: To investigate the application of tirofiban in patients with acute myocardial infarction complicated with diabetes and undergoing emergency interventional therapy. Methods: Two hundred patients with acute ST-segment elevation myocardial infarction (STEMI) complicated with diabetes who underwent percutaneous coronary intervention (PCI) and found to have high thrombus burden in coronary artery admitted to our hospital from September 2018 to September 2020 were selected as subjects, and were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The prognosis does not remain optimistic, with an in-hospital mortality rate of approaching 30% [ 2 ]. Studies have established that approximately 16.7% of patients with acute myocardial infarction have diabetes [ 3 ], and the combination of acute myocardial infarction and diabetes mellitus significantly increases the clinical mortality in patients [ 4 ]. An additional study has illustrated that disturbances in glucose metabolism due to fluctuations in blood glucose fluctuation are one of the leading factors in the mortality of patients with acute myocardial infarction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis does not remain optimistic, with an in-hospital mortality rate of approaching 30% [ 2 ]. Studies have established that approximately 16.7% of patients with acute myocardial infarction have diabetes [ 3 ], and the combination of acute myocardial infarction and diabetes mellitus significantly increases the clinical mortality in patients [ 4 ]. An additional study has illustrated that disturbances in glucose metabolism due to fluctuations in blood glucose fluctuation are one of the leading factors in the mortality of patients with acute myocardial infarction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 17 Tirofiban is a novel antiplatelet aggregation drug in clinical practice, which can inhibit platelet aggregation by inhibiting platelet membrane glycoprotein IIb/IIIa receptor. 18 Some scholars have pointed out that tirofiban can effectively inhibit platelet aggregation, improve cerebral microcirculation and promote the opening of cerebral collateral circulation in patients with ACI. 19 …”
Section: Discussionmentioning
confidence: 99%
“…17 Tirofiban is a novel antiplatelet aggregation drug in clinical practice, which can inhibit platelet aggregation by inhibiting platelet membrane glycoprotein IIb/ IIIa receptor. 18 Some scholars have pointed out that tirofiban can effectively inhibit platelet aggregation, improve cerebral microcirculation and promote the opening of cerebral collateral circulation in patients with ACI. 19 The results of our study also showed that the combination of edaravone dexborneol and tirofiban in the treatment of ACI could significantly reduce the levels of inflammatory factors in patients (p< 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The main pathological changes in acute myocardial infarction (AMI) are acute myocardial ischemia and necrosis. 1 AMIs can be divided into ST-elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI) according to ECG findings. 2 Both syndromes are caused by severe coronary artery stenosis or complete occlusion (mainly due to thrombosis on atherosclerotic plaques), and have similar clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%